Contents and Forewords - SIPATAHOENAN, Editor Journal (SIPATAHOENAN, 2015)
This journal, with ISSN ISSN 2407-7348, was firstly published on April 21, 2015. Since issue of April 2015 to date, the SIPATAHOENAN journal has been organized by the Central Board of APAKSI (Association of All Indonesia Sportsâ Experts and Practitioners) in Bandung; supported by KEMENPORA RI (Ministry of Youth and Sports of the Republic of Indonesia) in Jakarta; and published by Minda Masagi Press, as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The SIPATAHOENAN journal is published twice a year, i.e. every April and October.Â